Voltammetric determination of palmitic acid by electrode modified with reduced graphene oxide - Chin, Boon Ching; Abdullah, Jaafar; Yusof, Nor Azah (Springer, 2021)
Palm oil is one of the most produced and traded vegetable oils in the world recently. The quality of palm oil is very important to be examined and one of the quality indices is free fatty acid (FFA) content. Thus, in this study, an electrochemical technique for the determination of FFA as alternative to conventional method (titration method) has been explored. The electrochemical method was developed based on electrochemically reduced graphene oxide (rGO) deposited onto screen printed carbon electrode (SPCE) via drop-casting technique. The modified electrode was characterized by physico-chemical and electrochemical methods, respectively. The voltammetric behaviour of 2-methyl-1,4-naphthaquinone (VK3) in the presence of palmitic acid at the modified electrode was investigated in an acetonitrile/water (3:1) mixture containing 2.5 M lithium perchlorate (LiClO4). The electrochemical detection of palmitic acid was based on the voltammetric reduction of VK3 to form corresponding hydroquinone which is proportional to the concentration of palmitic acid. Under optimum condition, the developed method showed a good linear relationship in the concentration ranging from 0.192 mM to 0.833 mM with the detection limit of 0.079 mM. The developed sensor illustrates high sensitivity and rapid detection towards determination of FFA content in palm oil.